2018
DOI: 10.1159/000499854
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions for Weight Control Modified by Genetic Variation: A Review of the Evidence

Abstract: <b><i>Background/Aims:</i></b> Excess weight gain is a result of the interaction between diet, environment, and genes. Evidence suggests that responses to lifestyle interventions to manage weight are partially modified by genetic factors. This review is aimed at summarizing the current evidence from studies done on gene variants – single nucleotide polymorphisms (SNPs) – and intervention outcomes on weight loss and obesity-related traits. <b><i>Methods:</i></b> I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
0
7
0
1
Order By: Relevance
“…Further, onset of symptoms can be delayed and managed by lifestyle changes. The utilization of knowledge relating to human genetics is desired in public health services for disease prevention and health management, and may enable reduction of healthcare costs [ 42 , 43 ]; good effects have already been seen as a result of screening of some genetic disorders [ 44 ] and genetic testing for Alzheimer’s disease [ 45 ]. The results of our short-term education program suggested that it may also indirectly contribute to those ethical aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Further, onset of symptoms can be delayed and managed by lifestyle changes. The utilization of knowledge relating to human genetics is desired in public health services for disease prevention and health management, and may enable reduction of healthcare costs [ 42 , 43 ]; good effects have already been seen as a result of screening of some genetic disorders [ 44 ] and genetic testing for Alzheimer’s disease [ 45 ]. The results of our short-term education program suggested that it may also indirectly contribute to those ethical aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity is a useful strategy to reduce body weight [13] and related complications, such as high glucose levels, whose outcomes depend not only on the exercise type and duration but also on the individual’s genotype [14, 15]. Some studies have assessed interactions between physical activity and macronutrient distribution on management of chronic diseases [16-18], but the results are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Tan et al, 84 however, was pessimistic about the use of genetic data for predicting weight loss. In their review of 36 studies conducted in 13 different countries with a total of 15 931 participants aged between 19 and 70 years of age, 26 genes and 64 single nucleotide polymorphism (SNPs) were examined for their relation to the reduction of body weight and improvement in metabolic risk factors in response to diet, exercise and lifestyle interventions.…”
Section: Future Directions For Individualized Treatmentmentioning
confidence: 99%